Exploring responsibilities for delivering quality nursing care using the Healthcare Quality Framework. Issue 1 (February 2023) - Cusack, Lynette; Thornton, Karleen; Brytan, Janelle
ABSTRACT: Background: Nurses have a professional obligation to provide safe, quality practice responsive to the needs of people they care for. The Healthcare Quality Framework designed to describe nurses' responsibilities in healthcare quality, was utilised to explore nurses' perceptions of quality care to improve patients' experience. Methods: Qualitative exploratory descriptive design conducted in two stages, in a South Australian metropolitan health service. First stage involved eight focus groups attended by 41 participants, comprising enrolled and registered nurses delivering direct patient care. Discussions recorded digitally, transcribed and thematically analysed. Second stage involved mapping and synthesis of focus group data against 61 elements located across seven domains of the Healthcare Quality Framework. Findings: First stage: Eleven themes identified that described nurses' skills and responsibilities to deliver quality nursing care. Most frequently reported were effective communication, delivering basic elements of care, team work, supportive environment and compassionate, respectful, dignified care. Second stage: Out of 61 elements of the Healthcare Quality Framework, twenty-four gaps were identified related to domains: Management of the Environment; Promotion of Safety; Clinical Leadership and Governance. Discussion and Conclusion: Nurses' narratives focused on delivery of quality care within their unit/ward. Participants did not identify how they may influence the healthcare team and health service to improve care. The Healthcare Quality Framework enabled a broader reflection on nurses' responsibilities for quality care, identifying improvement initiatives. One initiative could be a specifically designed and evaluated mentorship program, based on the Healthcare Quality Framework that is accessible to all nurses after their transition year.